Role of brain cholecystokinin in neuronal homeostasis: rediscovering novel functions of an old neuropeptide - Santiago J. Ballaz (Exploration of Drug Science)
Cholecystokinin (CCK) is the most prevalent neuropeptide in the brain, where it affects satiety, pain modulation, memory, and anxiety. Its effects are mediated by GPCRs known as the “alimentary (gastrointestinal)” CCK1r (CCK 1 receptor) and the brain-specific CCK2r (CCK 2 receptor). While stress causes CCK to be released and full CCK2r agonists are potent panicogenic agents, specific CCK2r antagonists are ineffective at lowering human anxiety. As a result, the therapeutic potential of CCK as a target in psychiatry has been questioned. By compiling relevant new and historical scientific data retrieved from Scopus and PubMed, the aim of this review was to suggest a new function of CCK neurotransmission, the regulation of neuronal homeostasis during stress. Four lines of evidence were discussed that support the hypothesis of a CCK-driven neuronal homoestasis: (1) Homeostatic plasticity including synaptic scaling and intrinsic excitability; (2) its interaction with retrograde endocannabinoid signaling; (3) neuroprotective role; and (4) dynamic neuromodulation of CCK release. CCK functions as a crucial and essential molecular switch of neural circuits and neuroplasticity through its remarkable cell-specific modulation of glutamate and GABA release via CCK2r. CCKergic neurons are downstream of the activation of cannabinoid type-1 (CB1) receptors in order to generate and stabilize rhythmic synchronous network activity in the hippocampus. CCK is also released to modulate other neurotransmitters like dopamine and opioids when neuronal firing is intense during the processing of anxiety/fear, memory, and pain. CCK likely functions to restore baseline neuronal function and protect neurons from harm under these conditions. Anxiety, depression, and schizophrenia could result from compensatory plastic changes of the CCKergic system that go awry during neuronal homeostasis. This review concludes by examining the benefits of putative compounds that exhibit a combination of CCK agonist and antagonist activity at multiple locations within the CCKergic system, as well as off-targets in managing mental conditions.